2014
DOI: 10.1016/j.marpol.2013.11.017
|View full text |Cite
|
Sign up to set email alerts
|

A systematic approach towards the identification and protection of vulnerable marine ecosystems

Abstract: The United Nations General Assembly in 2006 and 2009 adopted resolutions that call for the identification and protection of vulnerable marine ecosystems (VMEs) from significant adverse impacts of bottom fishing. While general criteria have been produced, there are no guidelines or protocols that elaborate on the process from initial identification through to the protection of VMEs. Here, based upon an expert review of existing practices, a 10-step framework is proposed: 1) Comparatively assess potential VME in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
83
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(83 citation statements)
references
References 35 publications
0
83
0
Order By: Relevance
“…VME criteria are similar to those of ecologically and biologically significant areas (EBSAs) as defined by the UN Convention on Biological Diversity (CBD). EBSAs are "discrete areas, which through scientific criteria (similar to those listed for VMEs; see Ardron et al, 2014 for comparison of VME and EBSA criteria), have been identified as important for the health and functioning of our oceans and the services that they provide" (UNEP-WCMC, 2014; Cordes et al, 2016). The EBSA concept was developed under the United Nations Convention on Biological Diversity, which Trinidad and Tobago has been a signatory on since 1992 (Dunn et al, 2014;Cordes et al, 2016), but EBSAs have yet to be incorporated into any formal management structures (Dunn et al, 2014).…”
Section: Stewardship Of the Deep Ocean Of Trinidad And Tobagomentioning
confidence: 99%
“…VME criteria are similar to those of ecologically and biologically significant areas (EBSAs) as defined by the UN Convention on Biological Diversity (CBD). EBSAs are "discrete areas, which through scientific criteria (similar to those listed for VMEs; see Ardron et al, 2014 for comparison of VME and EBSA criteria), have been identified as important for the health and functioning of our oceans and the services that they provide" (UNEP-WCMC, 2014; Cordes et al, 2016). The EBSA concept was developed under the United Nations Convention on Biological Diversity, which Trinidad and Tobago has been a signatory on since 1992 (Dunn et al, 2014;Cordes et al, 2016), but EBSAs have yet to be incorporated into any formal management structures (Dunn et al, 2014).…”
Section: Stewardship Of the Deep Ocean Of Trinidad And Tobagomentioning
confidence: 99%
“…A number of United Nations General Assembly resolutions have been passed that require nation states and fishery management organizations to identify VMEs within their jurisdiction as one of the steps toward their protection (see Ardron et al, 2014 for details). Species or taxonomic groups have been identified that can be used as indicators of the presence of VMEs in particular ocean regions, in order to assist agencies responsible for their protection [e.g., the South Pacific Regional Fisheries Management Organization (SPRFMO) in the South Pacific region- Parker et al, 2009].…”
Section: Introductionmentioning
confidence: 99%
“…Although these are the general patterns, high inter-annual variability has been observed in this region Habitat suitability models based on reliable environmental data is the most cost-effective and timely solution for determining the location of vulnerable marine ecosystems in the Azores. Actually, such models are recognized to be fundamental when designing management plans for protecting vulnerable marine ecosystems from anthropogenic impacts such as fishing (Ardron et al, 2014). Furthermore, oxygen levels, temperature, aragonite and calcite concentrations at the seabed have been important parameter for explaining the distribution of black corals (Yesson et al, in press) and other cold-water coral species (e.g., Davies and Guinotte, 2011;Yesson et al, 2012;Bostock et al, 2015).…”
Section: Discussionmentioning
confidence: 99%